The Role of C-Reactive Protein and Fibrinogen in the Development of Intracerebral Hemorrhage: A Mendelian Randomization Study in European Population - Wang, Biyan; Zhang, Xiaoyu; Liu, Di; Zhang, Jie; Cao, Mingyang; Tian, Xin; Maranga, Isinta Elijah; Meng, Xiaoni; Tian, Qiuyue; Tian, Feifei; Cao, Weijie; Wang, Wei; et al. (Frontiers in Genetics, 2021)
Background: The causal association of systemic inflammation on intracerebral hemorrhage (ICH) remains uncertain. We investigated the causal associations of C-reactive protein (CRP) and fibrinogen with ICH using two-sample mendelian randomization. Method: We used single nucleotide polymorphisms (SNPs) associated with CRP and fibrinogen as instrumental variables. The summary data on ICH was obtained from International Stroke Genetics Consortium (1,545 cases and 1,481 controls). Two-sample mendelian randomization estimates were performed to assess with inverse-variance weighted (IVW) and sensitive analyses methods including weighted median (WM), the penalized weighted median (PWM), Pleiotropy Residual Sum and Outlier (MR-PRESSO) and outlier approaches. MR-Egger regression was used to explore the pleiotropy. Results: The MR analyses indicated that genetically predicted CRP was not associated with ICH, with an odds ratio (OR) of 1.263 [95% confidence interval (CI), 0.935-1.704, P = 0.127]. Besides, genetically predicted fibrinogen concentrations were not associated with a potential increase in risk of ICH, with an OR of 0.879 (95% CI, 0.060-18.281, P = 0.933). No evidence of pleiotropic bias was detected by MR-Egger. The findings were overall robust in sensitivity analyses. Conclusions: Genetically increased CRP and fibrinogen were not associated with increased risk of ICH, suggesting that efforts to influence CRP and fibrinogen level are unlikely to have effects on ICH.